Evaluation of Beta-2 Integrin and Platelets Roles in Sickle Cell Disease Pathogenicity in Basrah Governorate Patients (Baghdad Science Journal, 2023)
Sickle cell disease (SCD) comprises an inherited blood disorder that is life long and affects many people globally. In spite of the development in treatment, SCA is a considerable cause of mortality and morbidity. The present study tries to assess the role of leukocytes represented by β integrin(CD18) and platelets and their productivity in the pathogenicity of disease during  the steady state and crisis in comparison with the healthy as-control group, SCD patients (15) enrolled during crisis and steady state (follow up) showed a significant increase in leukocytes and platelets cells productivity during crisis when compared to the steady state and in the steady state when compared to the healthy control group . In this study, SCD pathophysiology in  steady state and crisis affected by the platelets account and leukocyte  activation triggered by inflammatory factors and reflex on the adherence and attachment between cells and blood vessel  led to vascular occlusion (VOC).